THE ROLE OF WOMEN IN THE WINNING OF THE 2019 ELECTION (STUDY ON THE NATION WOMEN'S DPP) - Kulsum, Nieke Monika (Universitas Nasional, 2020)
The research focus on the democratic party that held in 2019. The Legislative Election (Pileg) and Presidential Election (Pilpres) activities were simultaneously for the first time. There were many various kinds of things done by parties in Indonesia in preparing themselves to face the national event. The 2018 elections will be a new era for women in leadership. Several female candidates in the 2018 elections is a sign of democracy in Indonesia which has reached a significant maturation stage compared to previous years. Society increasingly has the freedom to determine the figures deemed appropriate to lead the region, including the courage to support women candidates. These included the election of Nahdliyin women such as Khofifah Indar Parawansa as East Java Governor, Chusnunia Chalim as Deputy Governor in Lampung, Ana Muawanah as Bojonegoro Regent, completing other women who were equally elected as regional heads in the 2018 elections. The study was a qualitative study, gathering data is done through interviews, documentation studies and literature studies.